THE INFLUENCE OF STEAM DRYING PROCESS ON COMBUSTION BEHAVIOR OF INDONESIAN LOW-RANK COALS - Datin Fatia Umar; Suganal Suganal; Ika Monika; Gandhi Kurnia Hudaya; Dahlia Diniyati (Puslitbang tekMIRA, 2020)
Steam drying process of the Low Rank Coals (LRCs) has been conducted to produce coal which is comparable with the High Rank Coal (HRC). Characterization of the raw and dried coals was carried out through proximate, ultimate, calorific value, Fourier Transform Infrared (FTIR) spectroscopy and Thermo Gravimetry-Differential Thermal Analysis (TG-DTA) to study the combustion behavior of the coals. This study used Indonesian low rank coals coming from Tabang (TKK coal) and Samurangau (SP coal), East Kalimantan. The results indicate that the calorific value of the dried coals increases significantly due to the decrease in moisture content of the coal. The FTIR spectrums show that the methylene-ethylene (RCH3/CH2) and aromaticity-aliphaticity ratios (Rar/al) of the dried coals increased while the ratio of RCO/ar decreased which reflect that the rank of the coals increased equivalent to the high rank coal (bituminous). Meanwhile, the TG-DTA indicates that the ignition temperature (Tig) and combustion rate (Rmax) of the dried coals increased. This analysis expresses that the dried coals produced by steam drying process have better combustion behavior due to the higher calorific value than those of the raw coals.